Software Strategies for Portable Computer Energy Management - Lorch, Jay; Smith, Alan Jay (IEEE Personal Communications Magazine, 1998)
Limiting the energy consumption of computers, especially portables, is becoming increasingly important. Thus, new energy-saving computer components and architectures have been and continue to be developed. Many architectural features have both high performance and low power modes, with the mode selection under software control. The problem is to minimize energy consumption while not significantly impacting the effective performance. We group the software control issues as follows: transition, load-change, and adaptation. The transition problem is deciding when to switch to low-power, reduced-functionality modes. The loadchange problem is determining how to modify the load on a component so that it can make further use of its low-power modes. The adaptation problem is how to create software that allows components to be used in novel, power-saving ways. We survey implemented and proposed solutions to software energy management issues created by existing and suggested hardware innovations.